Quality of life in young patients after cone reconstruction for Ebstein anomaly. (June 2019) - Sessions, Kristen L.; Van Dorn, Charlotte; Dearani, Joseph A.; Warring, Simrit; Leopold, Kaitlin; Wackel, Philip L.; Cetta, Frank; Johnson, Jonathan N.
Abstract: Objective: To evaluate the health status and quality of life of young patients who had cone reconstruction for Ebstein anomaly. Methods: We reviewed all patients who had cone reconstruction from 2007 to 2016 at our institution. Prospective surveys were mailed to all eligible patients. Quality of life was assessed using the PedsQL 4.0 Generic Core Scales, including four domains: physical, emotional, social, and school functioning. Results: Of 116 eligible patients, 72 (62%) responded. About 96% reported their health as excellent or good, and 52% were symptom-free. Only 37% of patients were taking any medications, the most common of which was aspirin (30%). Only 19% had been hospitalised for cardiac reasons following cone reconstruction. The average self-reported quality of life was 85.3/100, whereas the average parent proxy-reported quality of life was 81.8/100. There was no difference by self or parent proxy-report in quality of life between cone reconstruction patients and healthy children; however, quality of life was significantly better compared with children with other chronic health conditions. By self-report and parent proxy-report, 15.1 and 16.7% of patients were deemed "at risk" for reduced quality of life, respectively. Socially, 63/64 (98%) patients over 5 years old were either full-time students or working full-time. Conclusion: Children with Ebstein anomaly following cone reconstruction have excellent quality of life comparable with healthy peers and significantly better than other children with chronic health conditions. Families of children with Ebstein anomaly can expect excellent quality of life, long-term health status, and social functioning following cone reconstruction.